ANALYSIS OF SEGMENTING, TARGETING, POSITIONING (STP) MARKETING STRATEGY IN MSME BATIK - Dyah Setyawati; Sudarmiatin Sudarmiatin; Puji Handayati; Naswan Suharsono (Journal of Management Small and Medium Enterprises (SMEs), 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in driving economic growth; however, the increasing level of competition necessitates that business actors adopt effective and appropriate marketing strategies to sustain their competitiveness and achieve long-term success. This study aims to analyse the application of marketing strategies through the STP concept (Segmenting, Targeting, and Positioning) at Batik Krajan DW MSME in Karangploso. This research employs a descriptive qualitative method through observation, interviews, and documentation. The findings indicate that market segmentation includes batik enthusiasts, government institutions, schools, and tourists, with the main target being batik enthusiasts and government institutions. Positioning is carried out through the unique Batik Kawung Kates motif and involvement within the Hasta Padma batik industrial area. However, the implementation of the STP strategy has not been optimal, as indicated by fluctuating sales, low compliance of civil servants in wearing batik, and intense competition. These findings are expected to serve as a basis for strengthening the marketing strategy through a more optimal STP concept at Batik Krajan DW MSME. Keywords: Batik Krajan DW; MSMEs; STP Marketing Strategy